Use of the ABC Curve in Medicine Line Balancing: A Case Study at a Brazilian Pharmaceutical Distribution Center - N.P. Oliveira; D.G.O. Prado; R.H.G. Jesus (International Journal of Production Management and Engineering)
Within the logistics, especially in distribution centers, there is still use of manual activities, with great possibility of gaining productivity. This work aims to improve efficiency in the supply and separation stages by balancing drug lines using the ABC classification. For this, a case study was carried out in a large Brazilian retail pharmaceutical network, in which products of higher output were relocated in more strategic areas. Ergonomic gains, reduction of required manpower, greater assertiveness, and savings of two hours of work (25%) were the main results achieved. The study also made it possible to disseminate an accessible, automated and effective tool for line balancing on large scale inventories.